Akad Ariyah dan Akad Qardh Serta Pengintergrasiannya Dalam Analisis Kasus Kontemporer - Rahmah W., Zian; Islami, Nafisatuzahra Raysa; Purwaningrum, Dinda Alya; Hadid, Zubarul; Ningtyas, Dwi Sinta Febrian Wahyu; Hikmatusa'diyah, Agustin; Safitri, Nasya Almira; Kurniawan, Taufiq (AL-BAYAN: JURNAL HUKUM DAN EKONOMI ISLAM, 2025)
In social life, borrowing and lending activities are part of social interaction. However, many people still engage in borrowing and lending practices that are not in accordance with Islamic provisions. Islam regulates the provisions of contracts when carrying out mu'amalah activities, which are called akad. Akad is a relationship between ijab and qabul that gives rise to law. This study aims to examine and explore the concepts of Akad Ariyah (loan for use) and Qard (loan) in muamalah fiqh and their integration in contemporary cases. This study uses a qualitative method with a library research approach, with data obtained from the book Fiqh Muamalah, scientific journals, and Fatwa DSN-MUI. The results of the study show that the Ariyah contract (العارية) is a loan contract in the form of assistance with assets to be used without compensation and without changing the assets. The Qard contract (القرض) is the transfer of assets to be used and must be returned without additional interest (riba) or an equivalent amount. Therefore, we must understand these two contracts because the Ariyah and Qard contracts are very important for us to avoid usury practices and to maintain the principle of justice in conducting contemporary transactions.